Higher Order Mode Attenuation in Microstrip Patch Antenna with DGS H Filter Specification from 5 to 10 GHz Range - Souza,Francisco Ary Alves de (2020)
Abstract This work proposes the application of a slot in the ground plane, Defected Ground Structure (DGS), of a microstrip patch antenna. The application of this technique aims to attenuate higher-order excited modes without deteriorating the antenna parameters in the fundamental mode. The methodology for the design of the slot in H-format is presented, based on the physical dimensions of the microstrip patch antenna. The positioning of the DGS concerning the feed line was determined from a detailed parametric analysis. The antenna was designed for the fundamental mode at 2.45 GHz frequency. Two antenna prototypes were built, with and without DGS, and measurements of reflection coefficient, gain, and radiation pattern were performed. The measured results show that the application of DGS considerably attenuated higher-order excited modes. A good agreement between simulated and measured results is achieved.